L’art médiéval dans la construction de l’histoire dominicaine à l’époque moderne - Haude Morvan (Perspectives Médiévales)
The Early modern period was a time when history was becoming a true science, based on archival and material sources that scholars must prove as being authentic. The paper addresses the way seventeenth-eighteenth-century Dominican Friars used material and monumental sources to write the history of their own order. Which elements caught their attention, when they watch to their medieval heritage? With which methods and vocabulary did they describe it? How did they combine the information given by these material evidences with the archival sources? The analysis is based mainly on an unpublished documentation, mostly kept in the General Archive of the Order in Rome. First, the paper asks whether the Dominican scholars showed the feeling of a gap between present times and the « medieval » period, i.e. mainly the heroic times of their foundation during the 13th century. Then, the paper shows that the friars are often “antiquarians”, since they are interested in the material and cultural aspects of the past, with a focus rather on monumental and material sources than on archival ones. In a third part, the paper deals with some evidences of the awareness of some friars of the material heritage’s value, especially when they inventoried a threatened heritage through descriptions and drawings.